Molecular engineering enabling reversible transformation between helical and planar conformations by cyclization of alkynes. Issue 7 (23rd December 2020) - Yan, Lipeng; Ma, Weixin; Lan, Jingbo; Cheng, Hu; Bin, Zhengyang; Wu, Di; You, Jingsong
Abstract : One-pot synthesis of aza[4]helicenes is accomplished through two successive C–H activation/cyclizations, which exhibit on/off fluorescence switching through reversible transformation between helical and planar conformations. Abstract : Molecular engineering enabling reversible transformation between helical and planar conformations is described herein. Starting from easily available 2-(pyridin-2-yl)anilines and alkynes, a one-pot strategy is set up for the synthesis of aza[4]helicenes via two successive rhodium-catalyzed C–H activation/cyclizations. Helical pyrrolophenanthridiziniums can be transformed into planar conformations through the cleavage of acidic pyrrole N–H, leading to turn-off fluorescence. NMR spectra, single crystal X-ray diffraction and DFT calculations demonstrate that the formation of an intramolecular C–H⋯N hydrogen bond is beneficial to stabilize the pyrrole nitrogen anion of the planar molecule and provide increased planarity. The reversible conformation transformations can be finely adjusted by the electron-donating and -withdrawing groups on the π + -fused pyrrole skeleton in the physiological pH range, thus affording an opportunity for pH-controlled intracellular selective fluorescence imaging. Pyrrolophenanthridiziniums show turn-on fluorescence in lysosomes owing to the acidic environment of lysosomes and turn-off fluorescence out of lysosomes, indicating the occurrence of the deprotonation reaction outside lysosomes and the corresponding transformation from helical to planar conformations.